EMPLOYEE PERFORMANCE: THE MODERATING ROLE OF LEADER-MEMBER EXCHANGE (A STUDY ON THE FAST-FASHION RETAIL INDUSTRY) - William Widjaja; Devi Rahnjen Wijayadne; Franziska Maria Renz (Jurnal Manajemen dan Kewirausahaan, 2023)
This study investigated the knowledge gap in the retail sector by exploring the relationship between job satisfaction, counterproductive work behavior, and organizational citizenship behavior on employee performance moderated by leader-member exchange. The quantitative study used a survey method to collect data with purposive sampling and technique. The survey was conducted on 150 employees from 17 Jakarta, Bogor, Depok, Tangerang, and Bekasi (JABODETABEK) outlets. The data was analyzed using the structural equation modeling partial least square technique processed with smart-pls 3.3.3 tools. The study's findings were as follows: job satisfaction negatively and significantly affected counterproductive work behavior, counterproductive work behavior affected organizational citizenship behavior, and organizational citizenship behavior positively and significantly affected employee performance. In the meantime, leader-member exchange moderated job satisfaction's effect on counterproductive work behavior and employee performance but did not moderate counterproductive work behavior's effect on organizational citizenship behavior. The research had novelty from the aspect of a specific sample characteristic: the employees of the fast-fashion retail. It used a conceptual framework that combined theories of job satisfaction, counterproductive work behavior, organizational citizenship behavior, and leader-member exchange to explain employee performance, which had never been done in previous studies in the fast-fashion retail context.